Elucidating nuclear motions in a plant sunscreen during photoisomerization through solvent viscosity effects. Issue 31 (27th July 2017) - Horbury, M. D.; Quan, W.-D.; Flourat, A. L.; Allais, F.; Stavros, V. G.
Abstract : We explore the effects of solvent viscosity on the trans – cis photoisomerization of sinapoyl malate, which is utilized as a sunscreen molecule in plants. Abstract : We explore the effects of solvent viscosity on the trans – cis photoisomerization of sinapoyl malate, which is utilized as a sunscreen molecule in plants. Our results demonstrate that viscosity has a significant effect on the timescale for isomerization, providing insight into the nuclear motions involved. The ramifications of these findings are discussed with reference to sinapoyl malate's in vivo photoprotection properties.